2020
DOI: 10.1002/cpp.2501
|View full text |Cite
|
Sign up to set email alerts
|

Is the relationship between child abuse and suicide attempts mediated by nonsuicidal self‐injury and pain tolerance?

Abstract: Although there is evidence for an association of child abuse with lifetime suicidal behaviour, the underlying mechanisms remain unclear. In recent research, we found this relationship to be indirect and mediated by capability for suicide (CS). Emotional and sexual abuse were directly associated with CS. Based on the Interpersonal Psychological Theory of Suicide, the result for emotional abuse was surprising and raised the question for a missing link in this association. Consequently, this study examines nonsui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
2
8
0
1
Order By: Relevance
“…In contrast, Schönfelder et al. (2021) found no subtype of abuse to be associated with CS but NSSI showed correlations with both, child abuse and suicide attempts.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In contrast, Schönfelder et al. (2021) found no subtype of abuse to be associated with CS but NSSI showed correlations with both, child abuse and suicide attempts.…”
Section: Introductionmentioning
confidence: 88%
“…In addition to the immense impact it has on physical health (Afifi et al., 2008, 2016), child abuse also has substantial adverse lifelong effects on mental health (Afifi et al., 2008; Norman et al., 2012). Correspondingly, research has shown that experiences of abuse during childhood are related to various self‐destructive behaviours such as substance abuse (Jaffee, 2017), non‐suicidal self‐injury (NSSI; Brown et al., 2018; Schönfelder et al., 2021), suicidal ideation (Bruwer et al., 2014; Gibb et al., 2001), and suicidal behaviour (Liu et al., 2017; Norman et al., 2012; WHO, 2016; Zatti et al., 2017). As these results demonstrate, the relationship between child abuse and suicidality has been shown repeatedly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations